(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
This article studies the territories to which the inhabitants of the cities of north-central Italy had a sentiment of belonging between the 11th and 13th centuries. At the beginning of the period, they were particularly attached to the county or to a subdivision of the diocese, the urban piviere, while feeling that they belonged to territories of a more socio-cultural nature. However, in the 12th and early 13th centuries, the communes reorganized the urban territory and, in doing so, the sense of belonging of the inhabitants. The municipal institutions established a two-level system: large urban portions comprising part of the walls and sub-districts, corresponding more or less to the parishes. If this transformation of urban administrative territories greatly affected the identity of the city’s inhabitants and their attachment to the commune and its institutions, it did not lead to a reduction in the number of socio-cultural territories. The overlapping of these numerous territories thus led the city’s inhabitants to consider themselves as belonging to several territories and, therefore, to combine these territorial identities that they unfailingly evoked according to their interests. From the twelfth century, This intricate interplay of cospatialities became one of the key elements of the identity of the city’s inhabitants, as well as the prism underlying their way of thinking, how they expressed themselves and acted.